2022
DOI: 10.1186/s12870-022-03438-7
|View full text |Cite
|
Sign up to set email alerts
|

Population structure analysis to explore genetic diversity and geographical distribution characteristics of cultivated-type tea plant in Guizhou Plateau

Abstract: Background Tea plants originated in southwestern China. Guizhou Plateau is an original center of tea plants, and is rich in germplasm resources. However, the genetic diversity, population structure and distribution characteristics of cultivated-type tea plants in the region are unknown. In this study, we explored the genetic diversity and geographical distribution of cultivated-type tea accessions in Guizhou Plateau. Results We used 112,072 high-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…In this study, a positive value of Tajima’s D was detected in the wild tea plant population, suggesting that the wild tea plant population underwent population bottlenecks and/or balancing selection (Table 2 ). Fst (differentiation coefficient) is used as a measure of population structure; Fst values of 0–0.05 and 0.05–0.15 indicate little and moderate divergence, respectively [ 25 , 26 ]. In this study, the Fst value of C. gymnogyna and C. tachangensis was 0.075, suggesting that the moderate divergence occurred in the wild tea plant population between C. gymnogyna and C. tachangensis (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, a positive value of Tajima’s D was detected in the wild tea plant population, suggesting that the wild tea plant population underwent population bottlenecks and/or balancing selection (Table 2 ). Fst (differentiation coefficient) is used as a measure of population structure; Fst values of 0–0.05 and 0.05–0.15 indicate little and moderate divergence, respectively [ 25 , 26 ]. In this study, the Fst value of C. gymnogyna and C. tachangensis was 0.075, suggesting that the moderate divergence occurred in the wild tea plant population between C. gymnogyna and C. tachangensis (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that Fst in the range of 0.00 to 0.05 indicate little divergence, Fst in the range of 0.05 to 0.15 indicate moderate divergence and 0.15 to 0.25 indicate large divergence [ 26 , 27 ]. The pairwise Fst was analyzed among three inferred groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the genetic distance matrix of 229 individuals in the wild and ex situ populations was calculated using Plink. The sampling intensity of previous core germplasms of woody plants usually ranges between 30% and 45%(Duan et al, 2017;Lv et al, 2020;Wang et al, 2016;Zhao et al, 2022). In the Camellia genus,Zhao et al (2022) determined a sampling intensity of 33.6%…”
mentioning
confidence: 99%